Life after lockdown: making workplaces safer - Sharma, Sarita; Ukey, Ujwala; Rathod, Pragati; Patil, Sonali; Narlawar, Uday (International Journal Of Community Medicine And Public Health, 2020)
Considering the relentless nature of spread of COVID-19 with no end in sight, many countries have now decided to lift off some restrictions and allow some non-essential services, at least in those areas which are not severely hit by COVID-19. Lack of planning for reopening can result in a cascade of failures as employers are not aware of how to address challenges of COVID-19 with limited resources under pandemic conditions. Undoubtedly this demands lots of modifications at the workplaces that will require various strategies including primarily development and implementation of the plan and maintaining and revising it from time to time. Thorough literature search was conducted for this purpose on varied search engines applying key terms as ‘COVID-19’ and ‘return to work’ and ‘safe workplaces’ and ‘life after lockdown’ which revealed different elaborate guidelines framed by various competent authorities in relation to reopening workplaces after lockdown of COVID-19 pandemic. The current review is an attempt towards combining and presenting broad guidelines for workplaces in a simplified manner.